PROFITABILITY AND VALUE RELEVANCE: THE CASE OF LISTED FINANCIAL INSTITUTIONS IN BANGLADESH - Shamem Ara Mili; Bishawjit Chandra Deb; Nayan Kumar Sadhu; Fathyah Hashim; Md. Nazrul Islam (International Journal of Accounting, Finance and Business, 2023)
This study has investigated the profitability and its value relevance in the selected listed financial institutions (FININSsFININSs) of Bangladesh. In view of that, the study has examined the net profit margin (NPM), earnings per share (EPS), return on assets (ROA) and return on equity (ROE) of the selected financial institutions over a period of 5 years from 2015 to 2019. Using several statistical tools like mean, coefficient of variation (CV), and t-test, the study has found that the overall profitability position of the selected financial institutions is satisfactory. The study has also adopted POLS and FE model to examine the value relevance of profitability in the sample financial institutions. Regression results (STATA output) have shown that EPS has a positive significant impact on market value per share (MVPS); ROA has a negative significant impact on MVPS, whereas NPM and ROE have no effect on MVPS. It is also found that the profitability position of DBH is best among the sample FININSs over the study period followed by GSPFINANCE, UNITEDFIN, PHOENIXFIN and BAYLEASING respectively. FININSs play a significant role to the economic expansion of a country. Thus, to analyze the profitability position and its value relevance in the listed FININSs of Bangladesh might have a great importance to concerned investors, managers and other stakeholders.